Model Pendekatan Kecurangan Laporan Keuangan dengan Aalisis Heptagon Fraud - Naupally, Mohamad Arya (Tauhidinomics: Journal of Islamic Banking and Economics, 2023)
The purpose of this study, to examine the effect of heptagon fraud on fraudulent financial statements. The population in this study is a consumer goods industry sector manufacturing company for the period 2019 - 2024, with purposive sampling obtained as many as 222 sample data. This study uses the PLS - SEM analysis method using SmartPLS 3.0 software. Results of this study indicate that pressure, opportunity, and rationalization have a significant effect on fraudulent financial statements. Meanwhile, competence, arrogance, culture, and social assistance funds don’t have a significant effect on fraudulent financial statements.